2020
DOI: 10.3390/foods9101366
|View full text |Cite
|
Sign up to set email alerts
|

Latilactobacillus curvatus: A Candidate Probiotic with Excellent Fermentation Properties and Health Benefits

Abstract: Latilactobacillus curvatus is a candidate probiotic that has been included in the list of recommended biological agents for certification by the European Food Safety Authority. According to the published genomic information, L. curvatus has several genes that encode metabolic pathways of carbohydrate utilization. In addition, there are some differences in cell surface complex related genes of L. curvatus from different sources. L. curvatus also has several genes that encode bacteriocin production, which can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 136 publications
2
14
0
1
Order By: Relevance
“…L. fermentum (Type-III), L. curvatus and L. acidophilus showed the highest (p < 0.05) pH reduction in both cow's and buffalo's milk. In L. curvatus species several genes associated with metabolic pathways encoding proteins that are involved with carbohydrate utilization were identified (Chen et al, 2020) and it may result in high production of acids in milk leading to a high pH reduction as seen in the present study. In both situations, L. fermentum (Type-I), showed the lowest (p < 0.05) pH reduction and it may be associated with its facultative heterofermentative nature which uses substrates to produce both acid and non-acidic substances depending on the situation.…”
Section: Determination Of Milk Coagulation Ability Of the Isolatessupporting
confidence: 56%
“…L. fermentum (Type-III), L. curvatus and L. acidophilus showed the highest (p < 0.05) pH reduction in both cow's and buffalo's milk. In L. curvatus species several genes associated with metabolic pathways encoding proteins that are involved with carbohydrate utilization were identified (Chen et al, 2020) and it may result in high production of acids in milk leading to a high pH reduction as seen in the present study. In both situations, L. fermentum (Type-I), showed the lowest (p < 0.05) pH reduction and it may be associated with its facultative heterofermentative nature which uses substrates to produce both acid and non-acidic substances depending on the situation.…”
Section: Determination Of Milk Coagulation Ability Of the Isolatessupporting
confidence: 56%
“…The literature data showed that different isolates of Lb. curvatus exhibit beneficial role in dyslipidemia and obesity 26 . Moreover, in the case of Lb.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Z12 had no lytic activity against sheep blood erythrocytes, so it can be considered a safe candidate for probiotics. Generally, LAB are sensitive to broad-spectrum antibiotics (e.g., tetracycline and chloramphenicol), macrolides (azithromycin), glycopeptides (vancomycin), and β-lactam antibiotics (e.g., ampicillin, penicillin, and cephalothin) but resistant to aminoglycosides (e.g., streptomycin and gentamicin) ( 25 , 32 ). However, in our study, some contradictory resistance results were found for Z12 , which displayed resistance to ampicillin, vancomycin, tetracycline, and chloramphenicol but sensitivity to penicillin G and cefamandole and intermediate resistance to azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are various opinions as to whether probiotics showing resistance to specific antimicrobials are desirable since antimicrobial-resistant probiotics also have potentially negative effects, such as the transfer of resistance to intestinal pathogens or antibiotic-induced diarrhea ( 25 ). However, previous studies have shown that mobile elements such as phage, transposases and insertion sequences were not found in the complete genomes of L. curvatus SRCM103465 (CP035110.1), L. curvatus MARS6 (CP022474), and L. curvatus 20,019 (CP026116.1), as well as their upstream and downstream 5 kbp sequences downloaded from NCBI, indicating a low transfer risk of antimicrobial resistance genes in L. curvatus species ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation